2010
DOI: 10.1016/j.juro.2010.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Urinary Tract Infection After Renal Transplantation and its Impact on Graft Function in Children and Young Adults

Abstract: In this study there was no correlation between a history of urinary tract infection (either before or after transplant) and decreased graft function. History of pre-transplant urinary tract infection was suggestive of urinary tract infection after transplant. Patients with urological causes of renal failure may be at increased risk for post-transplant urinary tract infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
8
23
1
2
Order By: Relevance
“…Additionally, all boys in the present study were circumcised early in infancy as a routine social and religious practice. However, other studies did not report a higher incidence of UTI in girls . A higher incidence of UTI Post‐Tx was also reported in children with LUTD .…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, all boys in the present study were circumcised early in infancy as a routine social and religious practice. However, other studies did not report a higher incidence of UTI in girls . A higher incidence of UTI Post‐Tx was also reported in children with LUTD .…”
Section: Discussionmentioning
confidence: 82%
“…Several studies concluded that the presence of lower urinary tract abnormality is a significant risk factor for posttransplant UTI [12,13]. However the prevalence of UTI in LUTD (þ) patients varies widely in the literature due to many factors, such as differences in the definition of UTI, agents chosen for prophylaxis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous risk factors have been identified including young age, Caucasian race, male gender, specific immunosuppressive medications, and type of organ transplanted [19–22]. However, primary EBV infection is considered to be the most important [19, 20, 23, 24].…”
Section: Epstein Barr Virusmentioning
confidence: 99%